Update on Biology of Cutaneous T-Cell Lymphoma - Phyo, Zaw H.; Shanbhag, Satish; Rozati, Sima (Frontiers in Oncology, 2020)
Cutaneous T cell lymphomas (CTCL) are a heterogeneous group of lymphoid malignancies derived from skin-homing T cells. The diverse clinical and histological presentation can make the diagnosis challenging. The biology of CTCL remains to be elucidated and clear link between distinctive mutations and chromosomal alterations that would result in clonal T cell expansion have not been identified. Nevertheless, in the recent years, next generation sequencing has enabled a much deeper understanding of the genomic landscape of CTCL by uncovering genetic alterations in major pathways such as NFkB, MAPK and JAK/ STAT, cell cycle regulation and chromatin modification. Recent studies have again explored the role of antigen stimulation and its interaction with TCR rearrangement in disease progression. Additionally, single cell gene expression profiling is changing our understanding of patient-specific tumor landscape and its interaction with the surrounding microenvironment. These studies have paved the road for future investigations that will explore the functional relevance of these genetic alterations in the progression of disease. The ultimate goal is that these investigations lead to effective therapeutic targets with more durable clinical response and perhaps one day, cure of relapsing and refractory CTCL.